SATISFACTION OF THE HEAD OF A SCHOOL WITH THE CONDITIONS OF HIS PROFESSIONAL ACTIVITY: RESULTS OF THE RESEARCH - Lynov, Kostiantyn; Sabol, Diana (Continuing Professional Education: Theory and Practice, 2024)
The article is devoted to analysing the level of satisfaction of the head of a school in Kyiv with the conditions of his professional activity. The authors conducted a survey of respondents (school principals and their deputies) from three districts of Kyiv; the questions were grouped into 4 main groups: the direct personality of the head, his or her satisfaction with the relationship with participants in the educational process, certain aspects of the functioning of the educational institution and the material support itself. The survey involved 119 heads of general secondary schools, of whom 75.6% have more than 20 years of teaching experience). Our analysis showed that the manager is quite satisfied with the choice of the profession of an educator and the place of work, relatively satisfied with the work as a manager and the results of management activities. He believes that he has a high level of professional training. The head is most satisfied with the relations with the students of the school, the relations with the education administration, the teaching staff, and the least with the relations with the parents. The manager is satisfied with the level of psychological comfort in the educational institution and the educational program created by the institution for grades 5–7. Considers the level of executive discipline of pedagogical workers to be acceptable. Furthermore, he has an average level of satisfaction with the material base in the educational institution. The only thing the manager is not satisfied with is his salary level. Despite this, he remains committed to his professional activity, which corresponds to his professional identification, and remains in his profession. We emphasise the importance of continuing research on establishing relations between teachers and parents of students and ways to improve the material base of general secondary education institutions.